2015
DOI: 10.5902/1980509820592
|View full text |Cite
|
Sign up to set email alerts
|

INTRA-AND INTER-POPULATION VARIATION IN SEED SIZE AND DORMANCY IN <i>Schizolobium parahyba</i> (Vell.) Blake IN THE ATLANTIC FOREST

Abstract: Seed size and dormancy level were studied in 20 trees from two populations of Schizolobium parahybato evaluate how these characteristics occurbetween and within populations, and whether seed germination was affected by its morphometry. These two populations are located in the coastal (Paraty) or mountain (Miguel Pereira) regions in the state of Rio de Janeiro, Brazil. The seed morphometrictraits (length, width, thickness and weight) were measured. Germination with or without seedcoatdormancy treatment (mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…Generally, a large seed has greater reserve, which can be used by seedling in the early stages of growth (Baskin & Baskin, 2014). However, germination and seedling growth of species such as T. grandis (Khera et al, 2004) and S. parahyba (Freire et al, 2015) were not affected by seed size. In the present study, it was evident that higher means of cumulative emergence and emergence velocity index were associated with the physiological quality afforded by seed weight.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Generally, a large seed has greater reserve, which can be used by seedling in the early stages of growth (Baskin & Baskin, 2014). However, germination and seedling growth of species such as T. grandis (Khera et al, 2004) and S. parahyba (Freire et al, 2015) were not affected by seed size. In the present study, it was evident that higher means of cumulative emergence and emergence velocity index were associated with the physiological quality afforded by seed weight.…”
Section: Discussionmentioning
confidence: 89%
“…In general, high weight seeds exhibit higher germination capacity when compared to low weight seeds when exposed to low stress conditions (Genna & Pérez, 2016). For some forest species, it has been shown that germination and vigor of seedlings are related to seed weight (or size) (Du & Huang, 2008;Owoh et al, 2011;Socolowski et al, 2011a;Landergott et al, 2012;Kuniyal et al, 2013), but other species show no influence (Khera et al, 2004;Freire et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both populations presented a weak association between the variables ( Figure 4). Other studies, with another species from Fabaceae, also did not find associations between seed weight and seedling vigor [5], [46]. Seedling survivor and faster germinations associated with seed weight were also not observed [4].…”
Section: Seed Weight and Germinationmentioning
confidence: 83%
“…Segundo Freire et al (2015), mesmo dentro de populações de uma mesma espécie, o tamanho médio das sementes pode variar dependendo das perturbações do meio e do estágio da sucessão vegetal.…”
Section: Matrizunclassified